Appointment of Directors and Performance of Deposit Money Banks in Sub Saharan Africa: Do We Need More Executive or Non-Executive Directors? - Nzeribe, Nwaubani Anthony (Journal of Empirical Studies, 2019)
This study mainly examined the effect of Corporate governance on the performance of deposit money banks in Sub Saharan Africa (SSA). Specifically, the effect of appointment of more non- executive directors-BNEDDUM on return on assets (ROA) and net interest margin (NIM) of the banks in SSA was determined. Conversely, the work examined the effect of appointment of more executive directors on the ROA and NIM of the banks. Secondary data on six SSA countries and twelve banks collected for the period 2004 to 2016 were used. Panel data regression approach was employed to analyze the data. Fixed effects and Random effects models were adopted based on the results of Hausman tests. The study revealed among others that appointment of more number of non-executive directors has a positive but insignificant effect on ROA. It also indicated a strong positive correlation with both ROA and NIM. A hypothetical appointment of more executive directors showed a positive and significant effect on NIM while indicating the negative and insignificant effect on ROA. The positive effect of BNEDDUM on ROA coupled with its strong positive correlation with ROA and NIM seem to strongly suggest that appointment of more non-executive directors in deposit money banks in SSA is more beneficial to the banks than the appointment of more executive directors. However, the global conflict in the findings associated with appointment of directors is not yet fully resolved. The study recommends that while more non-executive directors may be appointed, banks in SSA must put in place internal control systems which promote a culture of professionalism in management.